Spatial distribution and source apportionment of polycyclic aromatic hydrocarbons in surface sediment of Langat River, Selangor, Malaysia - Mohamd Tahir, Nurul Afiqah (2012)
The rapid growth of infrastructure in Selangor, the Langat River has experienced change in land use and this subsequently caused the river to carry a significant load of material in the dissolved or particulate phases. PAHs can probably enter into the aquatic ecosystem through atmospheric transportation, storm water carrying surface runoff during rainy season, direct discharge of effluent from sewage treatment plants, or accidental spillage of oil from traffic boats or ships. This study was carried out on the collected surface sediments samples from 22 sampling locations at Langat River, Selangor. The objective of this study is to determine the concentration and pattern distribution of Polycyclic Aromatic Hydrocarbons (PAHs) on the surface sediments. Besides that, this work have identified the possible anthropogenic sources of PAHs by using Principal Component Analysis (PCA) followed by the apportionment of PAH sources using Multiple Linear Regression (MLR). The samples underwent Soxhlet Extraction (SE) method to extract the target compounds using dichloromethane (DCM). Then, the extracts were cleaned and separated using two steps of column chromatography with silica gel. The concentrations of 23 individual PAHs were determined and quantified using gas chromatography mass spectrometry (GC-MS) detector. The total concentrations of PAHs were ranged from 60.61 to 426.07 ng/g dry weight with a mean of 221.43 ng/g dry weight. This finding revealed that the level of PAHs pollution in Langat River fell within low to moderate. Cluster analysis (CA) showed that six sampling locations can be classified as having high pollution loading of PAHs due to the rapid growing in residential areas and industrial area as well as shipping boat traffic. Five possible PAHs sources were generated: automobile emission (70.86%), spillage from petroleum derivative product (20.06%), unburned fuel from transportation (5.07%), wood combustion (2.79%); and road dust (1.22%). This study uncovered the usefulness of PCA as an alternative technique in order to identify the PAHs sources. Besides that, MLR of the generated data (factor scores) from PCA was used to apportion the PAHs sources. The strong correlation between observed and predicted total concentration of PAHs proved that MLR is convincing technique in identifying the percentage contribution of PAHs sources.